2020
DOI: 10.1111/jcms.13112
|View full text |Cite
|
Sign up to set email alerts
|

The Rule of Law and Access to the Courts for EU Migrants

Abstract: The ability of workers generally to enforce their labour rights in the UK has been a matter of ongoing discussion over a number of years. However, the dominance of the topic of immigration in the Brexit debates, along with questions surrounding the need for, and position of, EU migrant workers in the British labour market, has brought into sharp focus the issues facing the most vulnerable workers in their ability to enforce their employment rights. This, we argue, poses a serious challenge to the rule of law a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The former focused on political science, economics and law, the latter also drawing in more anthropology, sociology, socio-legal studies and geography. Taken together, UKICE and Governance after Brexit cover a significantly broad range across the UK social sciences (in addition to this special issue, see, for example, the research reported in a Journal of Common Market Studies symposium on 'Impacts of Brexit on Civil Society, Parliament and Access to Justice'; Barnard & Fraser Butlin, 2020;Cygan et al, 2020;Minto, 2020;Wincott, 2020a).…”
Section: The Social Sciences and 'Impact'mentioning
confidence: 99%
“…The former focused on political science, economics and law, the latter also drawing in more anthropology, sociology, socio-legal studies and geography. Taken together, UKICE and Governance after Brexit cover a significantly broad range across the UK social sciences (in addition to this special issue, see, for example, the research reported in a Journal of Common Market Studies symposium on 'Impacts of Brexit on Civil Society, Parliament and Access to Justice'; Barnard & Fraser Butlin, 2020;Cygan et al, 2020;Minto, 2020;Wincott, 2020a).…”
Section: The Social Sciences and 'Impact'mentioning
confidence: 99%